2018
DOI: 10.1063/1.5051448
|View full text |Cite
|
Sign up to set email alerts
|

Gibbs free-energy differences between polymorphs via a diabat approach

Abstract: Polymorph free-energy differences are critical to several applications. A recently proposed diabat interpolation framework estimated free-energy differences between polymorphs by quadratic interpolation of diabats. This work extends the Zwanzig-Bennett relation to the NPT ensemble so that the diabats directly give Gibbs free-energy differences. We also demonstrate how the approach can be used in cases where the diabats are not parabolic. We illustrate the diabat method for Gibbs free-energy difference of zirco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…[135][136][137] A diabat free energy variant of LSMC makes further use of the exact Zwanzig-Bennet relationship 138,139 between free energy diabats. 140 This new method shows promising precision and efficiency for polymorphs of atomic systems, 141 as well as molecular systems 142 (requiring only two unbiased MD simulations in some cases). Our application to carbamazepine demonstrated precision at a level ±0.01 kcal mol -1 (±0.04 kJ mol -1 ) in computed free energy differences with just 5 ns of computing time per polymorph pair.…”
Section: Free Energies By Einstein Crystalmentioning
confidence: 99%
“…[135][136][137] A diabat free energy variant of LSMC makes further use of the exact Zwanzig-Bennet relationship 138,139 between free energy diabats. 140 This new method shows promising precision and efficiency for polymorphs of atomic systems, 141 as well as molecular systems 142 (requiring only two unbiased MD simulations in some cases). Our application to carbamazepine demonstrated precision at a level ±0.01 kcal mol -1 (±0.04 kJ mol -1 ) in computed free energy differences with just 5 ns of computing time per polymorph pair.…”
Section: Free Energies By Einstein Crystalmentioning
confidence: 99%
“…The use of a reference model system, namely the Einstein crystal, coupled with free energy perturbation (FEP) or thermodynamic integration (TI), provides an alternative method. These methods and some of their modifications have been implemented in MD packages. Some inherent errors in calculating relative free energies are removed by using the Lattice Switch Monte Carlo (LSMC) method, which has mainly been used in atomic solids. A further enhancement using the exact Zwanzig-Bennett relationship shows promise. Application to carbamazepine demonstrated precision at a level of ±0.01 kcal mol –1 (±0.04 kJ mol –1 ) in computed free energy differences with just 5 ns of computing time per polymorph pair . All of these methods are described in greater detail in Sections S2 and S3.…”
Section: Crystal Polymorph Selectionmentioning
confidence: 99%
“…Kamat and Peters demonstrated moderate efficiency advantages compared to the standard LSMC framework for the body-centered cubic and hexagonal close-packed phases of zirconium. 55 In this work, we extend the diabat method to non-orthorhombic crystals of flexible molecules. The mapping procedure we propose is system independent and easy to implement.…”
Section: The Journal Of Chemical Physicsmentioning
confidence: 99%
“…In previous work, we showed that the LSMC free energy profiles are superpositions of free energy diabats-one for the starting polymorph and one for the final polymorph with the two diabats crossing where the energy gap is zero. 54 We used (and generalized 55 ) the Zwanzig-Bennett relation 56,57 to calculate Helmholtz and Gibbs free energy differences (ΔF and ΔG, respectively) between the two polymorphs.…”
Section: Introductionmentioning
confidence: 99%